Epidemiology of Treponema pallidum, Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and herpes simplex virus type 2 among female sex workers in the Middle East and North Africa: systematic review and meta-analytics - Hiam Chemaitelly (439114) (2019)
Background The epidemiology of sexually transmitted infections (STIs) and the role of commercial heterosexual sex networks in driving STI transmission in the Middle East and North Africa (MENA) region remain largely unknown. Objective To characterize the epidemiology of Treponema pallidum (syphilis), Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and Herpes simplex virus type 2 (HSV-2) among female sex workers (FSWs) in MENA using an indepth quantitative assessment. Methods A systematic review on ten international, regional, and country-level databases was conducted, and reported following PRISMA guidelines. Pooled prevalences of current and/or ever infection for each STI were estimated using random-effects meta-analyses. Sources of between-study heterogeneity were investigated through random-effects meta-regressions. Results One T. pallidum incidence study and 144 STI prevalence studies were identified for 45812 FSWs in 13 MENA countries. The pooled prevalence of current infection was 12.7% (95% confidence interval (CI)=8.5%-17.7%) for T. pallidum, 14.4% (95% CI=8.2%-22.0%) for C. trachomatis, 5.7% (95% CI=3.5%- 8.4%) for N. gonorrhoeae, and 7.1% (95% CI=4.3%-10.5%) for T. vaginalis. The pooled prevalence of ever infection (seropositivity using antibody testing) was 12.8% (95% CI=9.4%-16.6%) for T. pallidum, 80.3% (95% CI=53.2%-97.6%) for C. trachomatis, and 23.7% (95% CI=10.2%-40.4%) for HSV-2. The multivariable meta-regression for T. pallidum infection demonstrated strong subregional differences, with the Horn of Africa and North Africa showing, respectively 6-fold (adjusted odds ratio (AOR): 6.4; 95% CI=2.5-16.7) and 5-fold (AOR=5.0; 95% CI=2.5-10.6) higher odds of infection than Eastern MENA. There was also strong evidence for declining T. pallidum odds of infection at 7% per year (AOR=0.93; 95% CI=0.88-0.98). Study-specific factors including diagnostic method, sample size, sampling methodology, and response rate, were not associated with syphilis infection. The multivariable model explained 48.5% of the variation in T. pallidum prevalence. Conclusions STI infection levels among FSWs in MENA are considerable, supporting a key role for commercial heterosexual sex networks in transmission dynamics, and highlighting the health needs of this neglected and vulnerable population. Syphilis prevalence in FSWs appears to have been declining for at least three decades. Gaps in evidence persist for multiple countries. Other Information Published in: Journal of Global Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.7189/jogh.09.020408